Water-Mediated Ion Selectivity in 2D MXene Channels - Yuan Zhang; Ming Chen; Teng Zhang; Tetiana Parker; Danzhen Zhang; Ruocun Wang; Hyunho Kim; Paweł Piotr Michałowski; Alexei Kornyshev; Yury Gogotsi (Journal of the American Chemical Society, 2026)
Abstract At the Ångström scale, water confined between two-dimensional layers behaves fundamentally differently from bulk water; this behavior governs ion transport in natural and engineered nanofluidic systems, yet the mechanisms by which confined water mediates selective ion transport remain poorly understood. As classical descriptions of aqueous ion transport break down under extreme confinement, experimental studies often face challenges in controlling both nanoconfined structure and surface chemistry, limiting our ability to explain and predict water and ion behavior in subnanometer channels and membranes. Here, we show that 2D Ti3C2Tx MXene nanosheets with precisely controlled interlayer spacing (0.9–5.0 Å), surface terminations, and electrode potentials provide a platform to systematically tune ion transport. Combined experimental measurements, including ion permeation, spatial secondary-ion mass spectrometry, and Fourier transform infrared spectroscopy, together with molecular dynamics simulations, reveal that ultranarrow confinement reorganizes confined water, imposes ion-specific energetic penalties for dehydration, and modulates ion–MXene interactions. Li+ permeation in horizontally aligned Ti3C2Tx channels is 2 orders of magnitude faster than in conventional vertically aligned MXene membranes, while electrochemical surface charge modulation further regulates ion selectivity. These coupled effects of confinement, surface chemistry, and water-mediated energetics define a transport regime beyond classical diffusion, offering design principles for artificial ion channels and high-performance membranes for ion separation, water desalination, and sustainable water treatment technologies.